2014
DOI: 10.1177/1545968314527352
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Training and Semantic Structuring Improves Remembering Future Events, Not Past Events

Abstract: Objectives. Memory training in combination with practice in semantic structuring and word fluency has been shown to improve memory performance. This study investigated the efficacy of a working memory training combined with exercises in semantic structuring and word fluency and examined whether training effects generalize to other cognitive tasks. Methods. In this double-blind randomized control study, 36 patients with memory impairments following brain damage were allocated to either the experimental or the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
3
14
0
2
Order By: Relevance
“…A more recent study in stroke patients tested the synergistic benefit from training WM coupled with a semantic structuring activity. The authors reported no benefit of training on their composite LTM measure [34]. The composite LTM measure was comprised of both short-delay and longdelay free recall scores from the CVLT.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A more recent study in stroke patients tested the synergistic benefit from training WM coupled with a semantic structuring activity. The authors reported no benefit of training on their composite LTM measure [34]. The composite LTM measure was comprised of both short-delay and longdelay free recall scores from the CVLT.…”
Section: Discussionmentioning
confidence: 97%
“…It is realistic to hypothesize that neurologically impaired populations would gain more from cognitive training programs considering their cognitive systems are not operating near maximum efficiency [13]. There is some support for this hypothesis in brain-injured patients [31][32][33][34]. The degree to which WM training transfers to improvements in LTM in this population is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors, like Klingberg (2010), Westerberg et al (2007), and Richter, Mödden, Eling, and Hildebrandt (2014), have argued that working memory may play a fundamental role for cognitive rehabilitation of other functions. On the other hand, Redick et al (2013) and Dunning, Holmes, and Gathercole (2013), found no transfer effects of working memory training on tests of other cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Greater working memory function predicts greater prospective memory function, and increasing working memory load worsens prospective memory performance (Smith, 2003; Smith & Bayen, 2005). As such, improvement in working memory may improve prospective memory (Richter, Modden, Eling, & Hildebrandt, 2015). Like prospective memory, working memory is impaired in substance-using populations (Crean, Crane, & Mason, 2011; Jovanovski, Erb, & Zakzanis, 2005; Martin et al, 2003; Mintzer & Stitzer, 2002; Murphy, Wareing, Fisk, & Montgomery, 2009; Ornstein et al, 2000; Rendell et al, 2009).…”
mentioning
confidence: 99%